Fungal diversities and community assembly processes show different biogeographical patterns in forest and grassland soil ecosystems - Wang, Min; Wang, Can; Yu, Zhijun; Wang, Hui; Wu, Changhao; Masoudi, Abolfazl; Liu, Jingze (Frontiers in Microbiology, 2023)
Soil fungal community has been largely explored by comparing their natural diversity. However, there is a relatively small body of literature concerned with fungal community assembly processes and their co-occurrence network correlations carried out across large spatial–temporal scales with complex environmental gradients in natural ecosystems and different habitats in China. Thus, soil fungal community assembly processes were assessed to predict changes in soil function in 98 different forest and grassland sites from the Sichuan, Hubei, and Hebei Provinces of China using high-throughput sequencing of nuclear ribosomal internal transcribed spacer 2 (ITS-2). The 10 most abundant fungal phyla results showed that Ascomycota was the most abundant phylum in forests from Sichuan province (64.42%) and grassland habitats from Hebei province (53.46%). Moreover, core fungal taxa (487 OTUs) represented 0.35% of total fungal OTUs. We observed higher fungal Shannon diversity and richness (the Chao1 index) from diverse mixed forests of the Sichuan and Hubei Provinces than the mono-cultured forest and grassland habitats in Hebei Province. Although fungal alpha and beta diversities exhibited different biogeographical patterns, the fungal assembly pattern was mostly driven by dispersal limitation than selection in different habitats. Fungal co-occurrence analyses showed that the network was more intense at Saihanba National Forest Park (SNFP, Hebei). In contrast, the co-occurrence network was more complex at boundaries between forests and grasslands at SNFP. Additionally, the highest number of positive (co-presence or co-operative) correlations of fungal genera were inferred from grassland habitat, which led fungal communities to form commensalism relationships compared to forest areas with having higher negative correlations (mutual exclusion or competitive). The generalized additive model (GAM) analysis showed that the association of fungal Shannon diversity and richness indices with geographical coordinates did not follow a general pattern; instead, the fluctuation of these indices was restricted to local geographical coordinates at each sampling location. These results indicated the existence of a site effect on the diversity of fungal communities across our sampling sites. Our observation suggested that higher fungal diversity and richness of fungal taxa in a particular habitat are not necessarily associated with more complex networks.